Intrapulmonary Mature Teratoma Presenting with Trichoptysis: A Rare Case Report - Nidzarsyah, Muhammad Mirsa; Hidayat, Moulid; Lestari, Rina; Widiasari, Komang Sri Rahayu; Fathana, Prima Belia; Santosa, Hilda; Kumaladewi, Baiq Ratna; Restuningdyah, Novia Andansari Putri; Arsatt, Maz Isa Ansyori (Indonesian Journal of Cancer, 2025)
Introduction: Intrapulmonary teratomas (IPT) are exceptionally rare, with only a handful of cases reported worldwide. The disease may lead to severe outcomes, such as massive hemoptysis, airway compression, and malignant transformation. Several international case reports on IPT focus on the diagnosis and surgical treatment approach. In Indonesia, only one case of intrapulmonary teratoma has been documented and analyzed for its radiological characteristics and anatomical pathology. Here, we present a case of mature IPT treated with surgery and adjuvant chemotherapy. To the best of our knowledge, this case is the second to be reported in Indonesia.Case Presentation: A 28-year-old man presented with a complaint of hemoptysis accompanied by clumps of hair (trichoptysis). Physical examination revealed no abnormalities. Chest X-ray and computed tomography (CT) thorax with contrast showed a right lung mass. The patient underwent lobectomy excision with the postoperative CT scan showing a residual mass. Furthermore, pathological findings confirmed a mature teratoma. Patients were then treated with adjuvant chemotherapy and showed clinical improvement.Conclusions: This case emphasizes the importance of including IPT in the differential diagnosis of hemoptysis, especially when trichoptysis–a rare but distinct symptom–is present. Although imaging tests like contrast-enhanced CT scans are crucial for identifying intrapulmonary masses, histological analysis is necessary for a conclusive diagnosis. The mainstay of treatment persists in surgical removal, and adjuvant chemotherapy may help control any remaining illness. This case emphasizes the importance of early detection and a multidisciplinary approach to enhance patient outcomes because it is one of the few documented IPT cases in Indonesia.